Assessment of the preparation and administration of oral medications to institutionalized children - Caroline Magna Pessoa Chaves; Francisca Elisângela Teixeira Lima; Ana Fátima Carvalho Fernandes; Érica Oliveira Matias; Patrícia Rebouças Araújo
ABSTRACT Objective: to evaluate the preparation and administration of oral medications to institutionalized children by nursing professionals. Method: quantitative study, developed from August to September 2016, in a shelter in Fortaleza, Ceará. 323 observations of preparation and administration of oral drugs were carried out. Interview and non-participant direct observation of the process of drug administration were performed, whose data were analyzed through descriptive statistics. Results: Of the 29 actions of preparation and administration of the drugs, ten were considered satisfactory. Sanitizing of hands before touching the pills occurred in only 5.2% of the observations and cleansing of the bottle for liquid drugs was performed in 23.8%. The actions "check the right child"; "checking medication with the prescription", and "check the right dose" obtained percentages below 15%. Conclusion: measures recommended by the literature for the administration of medication were not, in their clear majority, followed, making specific training and protocols necessary.